Powder properties and prebiotic activity of white dragon fruit (Hylocereus undatus) juice spray-dried using resistant maltodextrin - Yusof, Norzaida (2013)
Prebiotics which have been found effective in gastrointestinal normal flora proliferation and pathogen suppression occur naturally in fruits and vegetables including white dragon fruit (Hylocereus undatus). A study was, therefore conducted to produce white dragon fruit (WDF) powders through spray drying using resistant maltodextrin (RMD) and maltodextrin (MD) as wall materials. Resistant maltodextrin, which is a soluble fiber, was selected as a wall material to produce free-flowing WDF powder while MD was selected as the common wall material used in spray drying of fruit juice. Wall materials and drying conditions were assumed to influence powder properties and therefore, the objectives of this study were to investigate the effects of spray-drying conditions and two different wall materials, namely, MD and RMD, and to obtain optimum conditions for the production of the WDF powders by evaluating the physicochemical properties of the produced powders. To produce powder with RMD (WRMD), the following spray drying conditions were evaluated: an inlet temperature from 140 °C to 160 °C, an outlet temperature from 75 °C to 85 °C, and 20% to 30% RMD concentration. To produce powder with MD (WMD), the following spray drying conditions were studied: an inlet temperature from 150 °C to 170 °C, an outlet temperature from 75 °C to 85 °C, and 15% to 30% MD concentration. The produced powders were then evaluated for process yield, moisture content, water activity, solubility, hygroscopicity and bulk density. Results of the study demonstrated that the process yield of WDF powders increased with increasing inlet temperature and decreasing RMD and MD concentrations. Their moisture content and water activity decreased with increasing outlet temperature and increasing RMD and MD concentrations. Their solubility increased with increasing inlet and outlet air temperatures and increasing RMD and MD concentrations. Hygroscopicity of the powders increased with increasing inlet and outlet temperatures for both powders and decreased with increasing MD concentration for WMD powder. Bulk density of the powders decreased with increasing inlet and outlet temperatures for WRMD powder, whereas it decreased with increasing inlet temperature and MD concentration for WMD powder. RMD had nearly no effect on hygroscopicity and bulk density of the WDF powder. The optimum conditions to obtain a free-flowing WDF powder were at an inlet temperature of 153oC, outlet temperature of 82oC and 20% of RMD concentration, whereas 150 °C of inlet temperature, 75 °C of outlet temperature and 18% of MD concentration were the optimum conditions for production of WMD powder. The WDF powders produced using both RMD and MD at optimum spray drying conditions were then analysed for their physical properties, morphologies and glass transition temperatures, Tg. The results showed that RMD reduced the water activity and moisture content of the powder better than MD, while bulk density and true density of WRMD powder was higher than that of WMD powder. In addition, the particle size of WRMD powder was smaller than that of WMD powder and the morphology of the WRMD powder showed that it had a smooth surface compared to WMD powder where shrinkage and dent surfaces were observed. Although the Tg value of WMD powder was higher than that of WRMD powder, but their values were not significantly different (p>0.05). The potential of both powders as new prebiotic sources was then investigated whereby both powders were produced using the optimum spray drying conditions and then investigated for their ability to support the growth of Bifidobacterium longum BB536 and Lactobacillus casei Shirota. The growth of the 2 bacteria strains was determined every 6 h for 24 h with anaerobic incubation at 37 0C in six MRS media containing glucose, RMD, MD, WRMD, WMD and fructooligosaccharides (FOS) as substrates. The results indicated that all the substrates significantly (p<0.05) increased the growth of the probiotic bacteria; B.longum BB536 and L.casei Shirota and WRMD powder gave the highest bacterial count. Thus, the results indicated that WRMD has the potential as a new prebiotic source for the functional food industry.